KEMAMPUAN MALARISIDAL NANOPARTIKEL EKSTRAK DAUN JUWET (Syzygium cumini) SEBAGAI TERAPI AJUVAN PADA HISTOPATOLOGI HATI MENCIT (Mus musculus) PENDERITA MALARIA - Pujiyanto, Mahendra; Maslachah, Lilik; Triakoso, Nusdianto; Lazuardi, Mochamad; Anwar, Chairul; Legowo, Djoko (Journal of Basic Medical Veterinary, 2020)
The aimed of this study is to know malaricidal ability of nanoparticle juwet (Syzygium cumini) leaf extract as adjuvant therapy on liver histopathological of mice (Mus musculus) which infected by Plasmodium berghei. This research uses 30 mice which are divided into six treatment groups namely K0 (not infected without treated), K+ (infected without treated), K1 (infected and treated with chloroquin), K2 (infected and treated with juwet leaf extract), P1 (infected and treated with juwet leaf extract nanoparticle) and P2 (infected and combination treated with chloroquine and juwet leaf extract nanoparticle) which infected by 1x105 in 0.2 ml of Plasmodium berghei. The data were analyzed by Kruskal Wallis using SPSS and followed with Mann-Whitney test. This research result showed there was significant difference (p < 0.05) between K1 and P2, but did not showed significant difference (p > 0.05) with K+, K2 and P1. Based on this research, it could be concluded that nanoparticle juwet (Syzygium cumini) leaf extract as adjuvant therapy estimated can increase malaricidal ability in degeneration, necrosis, portal inflammation, Kupffer cell hyperplasia, sinusoidal congestion, and hemosiderosis in mice liver which infected by Plasmodium berghei.